High Prevalence of Mycoplasma pneumoniae and Chlamydia pneumoniae in Children with Acute Respiratory Infections from Lima, Peru - del Valle-Mendoza, Juana (2017)
Background Mycoplasma pneumoniae and Chlamydia pneumoniae are atypical pathogens responsible for pneumonia and a leading cause of morbidity and mortality in low income countries. The study objective is to determine the prevalence of this pathogens in Peruvian children with acute respiratory infections. Methods A consecutive cross-sectional study was conducted in Lima, Peru from May 2009 to September 2010. A total of 675 children admitted with clinical diagnoses of acute respiratory infections were tested for Mycoplasma pneumoniae and Chlamydia pneumoniae detection by polymerase chain reaction (PCR), and clinical symptoms were registered by the attending physician. Results Mycoplasma pneumonia was detected in 25.19% (170/675) of nasopharyngeal samples and Chlamydia pneumonia in 10.52% (71/675). The most common symptoms in patients with these atypical pathogens were rhinorrhea, cough and fever. A higher prevalence of Mycoplasma pneumoniae cases were registered in summer, between December 2009 and March 2010. Conclusions Mycoplasma pneumoniae and Chlamydia pneumonia are a significant cause of morbidity in Peruvian children with acute respiratory infections (ARI). Further studies should evaluate the use of reliable techniques such as PCR in Peru in order to avoid underdiagnoses of these atypical pathogens.